2010
DOI: 10.1111/j.1939-1676.2010.0557.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Ratio of CD8+ T Cells to Regulatory T Cells Associated with Decreased Survival in Dogs with Osteosarcoma

Abstract: Background Increased numbers of regulatory T cells (Treg) and decreased ratios of CD8+ T cells to Treg have been shown to correlate with decreased survival times (ST) in humans with certain malignancies. A possible connection between Treg and ST in dogs with cancer has not been investigated previously. Hypothesis The purpose of this study was to compare numbers of Treg and T lymphocyte subsets in dogs with osteosarcoma (OSA) to those of healthy dogs and to determine whether pretreatment values were associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
86
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(91 citation statements)
references
References 32 publications
3
86
1
1
Order By: Relevance
“…Interestingly, CD8 + /FOXP3 + -ratio in biopsies prior chemotherapy allows the identification of patients with prolonged survival confirming the results previously obtained in dogs [79,80]. The data revealed that patients with a CD8 + /FOXP3 + -ratio above 3.08 had an improved survival what strengthened the key function played by T-lymphocyte infiltrates in the pathogenesis of osteosarcoma [80].…”
Section: Lymphocytes Subpopulations In Osteosarcoma and Therapeutic Isupporting
confidence: 85%
See 1 more Smart Citation
“…Interestingly, CD8 + /FOXP3 + -ratio in biopsies prior chemotherapy allows the identification of patients with prolonged survival confirming the results previously obtained in dogs [79,80]. The data revealed that patients with a CD8 + /FOXP3 + -ratio above 3.08 had an improved survival what strengthened the key function played by T-lymphocyte infiltrates in the pathogenesis of osteosarcoma [80].…”
Section: Lymphocytes Subpopulations In Osteosarcoma and Therapeutic Isupporting
confidence: 85%
“…The data revealed that patients with a CD8 + /FOXP3 + -ratio above 3.08 had an improved survival what strengthened the key function played by T-lymphocyte infiltrates in the pathogenesis of osteosarcoma [80]. The identification of tumor-specific lymphocytes has led to the development of immunotherapeutic approaches based on the recovery of an effective and sustained anti-tumor immune response in patients [81,82].…”
Section: Lymphocytes Subpopulations In Osteosarcoma and Therapeutic Imentioning
confidence: 99%
“…Biller et al [27] show that T-cell effector (CD4 + and CD8 +) and regulatory (Treg) cells are responsible for both T lymphocytes and tumors. This study, the percentage and number of Treg, CD4+ and CD8+ cells were measured in blood by flow cytometry in lymph nodes and tumors by flow cytometry and compared between dogs with OSA and clinically healthy.…”
Section: Molecular Biology and The Search Of Biomarkers Of The Tumoramentioning
confidence: 99%
“…This professional informs the patient about his health condition in a clear way and makes him more involved in the treatment, being able to manage his own health, with changes of life habits in order to improve his prognosis [25][26][27][28][29]. In veterinary medicine, this professional is still not very present, especially in developing countries, and changes in patient's life habits depend on the actions of their owner, since he is responsible for their eating and physical activities outside the home environment.…”
mentioning
confidence: 99%
See 1 more Smart Citation